Diseminasi Karya Ilmiah untuk Meningkatkan Kemampuan Publikasi bagi Guru di SMP Negeri 2 Kayangan - Fatmawati, Any; Hajiriah, Titi Laily; Mashami, Ratna Azizah; Muttakin, Hairul (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
This dissemination activity aims to improve the publication skills of teachers at SMP Negeri 2 Kayangan, North Lombok Regency. The method of implementing this service is through outreach and demonstration. The instruments used to measure teachers' publication abilities are interviews and observations. Based on the results of observations and interviews during the training, around 70.59% of the training participants were able to show significant improvement, while the rest still needed to receive additional training so that they could produce scientific work correctly. The results of these observations were supported by the results of an interview with the Head of SMP Negeri 2 Kayangan who stated that this activity was very useful for teachers to motivate and improve their writing skills. They will apply the knowledge and skills in compiling scientific work obtained in the training, both individually and in groups to produce scientific work that can improve teacher professionalism. The results of the training activities showed that teachers were happy to receive refreshment regarding the importance of compiling scientific work.